APLIKASI PUPUK KOMPOS DAN PUPUK NPK PADA TANAMAN KELAPA SAWIT (Elaeis guineensis Jacq.) Di TBM – II - Anjani Kelana P; Hapsoh Hapsoh; Wawan Wawan (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The purpose of this study is to investigate the interaction effect compost fertilizer and multiple doses of NPK fertilizer as well as getting the best treatment between compost fertilizer and NPK fertilizer on the growth of oil palm (Elais guinensis Jacq.) immature phase II. This research has been conducted in experimental gardens Faculty of Agriculture, University of Riau Jl. Bina Widya Baru Simpang KM 12.5, Tampan, Pekanbaru. This research was conducted for 4 months starting in mid-Maret 2015 until mid-Juli 2016 , research was conducted with a Randomized complete Block Design (RCBD) factorial consisting of two factors, The first factor is the compost (K), which consists of three composision K0 = compost of 0 g/plant K1= TKKS and restaurant waste compost K2= rice straw compost and market waste second factor is the dose NPK fertilizer which consists of three levels ie M0 = NPK fertilizer dose of 0 g / plant M1 = NPK fertilizer dose of 750 g / plant M2 = fertilizer NPK dose of 1500 g / plant. Data were analyzed using ANOVA and extended with further research into the standard 5% DNMRT. Parameter observation is the increase of plant height (cm), number of leaves (leaf), girth (cm), midrib length (cm) and total frond (leaf). The results showed composting TKKS + garbage restaurants 7000 g / plant and NPK1500 gram / best plants at as height and length midrib while straw + junk market 7000 g / plant and NPK1500 gram / best plants for parameter number of leaves, girth and number of fronds immature oil palm plants. Keywords: Elaeis guineensis Jacq.,  Compost fertilizer, NPK fertilizer.